2022
DOI: 10.3390/ijms231911873
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Epigenomic Markers of the Arterial-Venous and Micro/Macro-Vascular Endothelial Heterogeneity within the Umbilical-Placental Bed

Abstract: Umbilical and placental vessels and endothelial cells (EC) are common models to study placental function and vascular programming. Arterio-venous differences are present in the umbilical endothelium; however, the heterogeneity of small placental vessels and the expression of potential micro- vs. macro-vascular (MMV) markers are poorly described. Here, we performed a meta-analysis of transcriptomic and DNA methylation data from placental and umbilical EC. Expression and methylation profiles were compared using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Conversely, consistent with findings reported in human (Krause, Costello et al., 2013), rat, mice and guinea‐pig (Herrera et al., 2017a; Krause et al., 2019) pregnancy, the NOS3 promoter in chicken arteries had a low density of CpG sites, in which both mean and site‐specific DNA methylation were decreased in embryos incubated under hypoxic conditions and restored by NAC treatment, correlating with changes in eNOS transcript levels. Studies focused on eNOS regulation show that basal eNOS expression is tightly and inversely regulated by NOS3 DNA methylation (Krause, 2021; Krause, Costello et al., 2013), an effect that has been confirmed by transcriptomic and genome‐wide data (Arenas et al., 2022). Combined, therefore, the data suggest that embryonic or fetal hypoxia drives epigenetic changes in key vascular genes, with a remarkable effect on NOS3 shared across diverse mammalian and non‐mammalian species.…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, consistent with findings reported in human (Krause, Costello et al., 2013), rat, mice and guinea‐pig (Herrera et al., 2017a; Krause et al., 2019) pregnancy, the NOS3 promoter in chicken arteries had a low density of CpG sites, in which both mean and site‐specific DNA methylation were decreased in embryos incubated under hypoxic conditions and restored by NAC treatment, correlating with changes in eNOS transcript levels. Studies focused on eNOS regulation show that basal eNOS expression is tightly and inversely regulated by NOS3 DNA methylation (Krause, 2021; Krause, Costello et al., 2013), an effect that has been confirmed by transcriptomic and genome‐wide data (Arenas et al., 2022). Combined, therefore, the data suggest that embryonic or fetal hypoxia drives epigenetic changes in key vascular genes, with a remarkable effect on NOS3 shared across diverse mammalian and non‐mammalian species.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have demonstrated that TNF-α stimulation contributes to endothelial-mesenchymal transition [32] and a proadhesive phenotype [7,15]. Notably, the transcriptional profile associated with TNF-α stimulation was comparable among different endothelial cell types, despite their considerable phenotypic differences [16,17,33], suggesting that this mechanism may affect, in a concerted manner, the endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic datasets were selected as previously described [16,17], applying PRISMA EQUATOR guidelines for the meta-analysis studies (http://www.equator-network.org/ reporting-guidelines/prisma, accessed on 30 June 2021). Using "Endothelial cells", "HU-VEC", "TNF-α", and "Affymetrix" as keywords, we explored GEO (Gene Expression Omnibus, http://www.ncbi.nlm.nih.gov/geo/, accessed on 30 October 2021; and OmicsDI, http://www.omicsdi.org, accessed on 30 October 2021).…”
Section: Experimental Designmentioning
confidence: 99%
“…Although fetal and from the placenta ( 75 ), HUVECs are not chorionic endothelial cells. Other studies highlighted significant transcriptomic distinctions between placental macro- and microvasculature, as well as between placental and umbilical endothelium ( 76 ). Despite the use of HUVECs herein, our model incorporates placental-derived stromal cells in a 3D microenvironment, enabling the development of fetoplacental-like microvessels.…”
Section: Discussionmentioning
confidence: 99%